2014
DOI: 10.4238/2014.january.24.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of radiotherapy on the treatment of patients with extensive stage small cell lung cancer

et al.

Abstract: ABSTRACT. Small cell lung cancer (SCLC) is an aggressive disease, in which more than 80% of patients present distant metastases at the time of first diagnosis. Chemotherapy is considered as the main treatment of extensive disease of SCLC (ED-SCLC), while the role of radiotherapy in the treatment of ED-SCLC is controversial. A case-control study was undertaken of patients diagnosed as ED-SCLC between 2004 and 2010. Fifty-eight patients with overall survival (OS) over 1 year were chosen, and another 58 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…As a result, leading to relapse and metastasis, therefore patients have higher recurrence 23 . Platinum-based chemotherapy combined with TRT significantly improved OS and PFS in ES-SCLC patients 4 , 16 , 20 , 24 , 25 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As a result, leading to relapse and metastasis, therefore patients have higher recurrence 23 . Platinum-based chemotherapy combined with TRT significantly improved OS and PFS in ES-SCLC patients 4 , 16 , 20 , 24 , 25 .…”
Section: Discussionmentioning
confidence: 92%
“…In the past when applying simple platinum-based chemotherapy as a standard treatment for ES-SCLC, thoracic radiotherapy was used only to palliate local symptoms and to improve quality of life 26 . Several clinical trials have demonstrated platinum-based chemotherapy combined with TRT to improve the prognosis of ES-SCLC patients 4 , 16 , 20 , 24 , 25 . According to the previous literatures 4 , 16 , 20 , 24 , 25 , the 2-year OS of patients with ES-SCLC who received chemotherapy plus TRT increased from 13% to 38%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of choice is the radiation therapy for the patients with extensive disease, for the metastatic sites and especially for the bones, the epidural, and the brain, which in this case the patients are treated with whole-brain radiation therapy. [70] The group of patients, with extensive disease, who submitted in chemotherapy and they revealed any response, they should be undergo assessment for thoracic radiation therapy. There is a big randomized trial, in which almost 500 patients after completing the chemotherapy schema, they randomized to receive radiation therapy or observation.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Moreover, the RTOG 0937 study and NTR1527 trial emphasized that TRT should be performed for ES-SCLC patients who responded to chemotherapy [8]. Several retrospective analyses also suggested that TRT in combination with chemotherapy was associated with long-term survival [9][10][11][12][13]. Recently, the additional use of TRT has been strongly advocated for certain ES-SCLC patients after chemotherapy treatment in the 2020 NCCN guidelines [14] and in the ASTRO 2020 guidelines [15].…”
Section: Introductionmentioning
confidence: 99%